PENGEMBANGAN BUKU AJAR BAHASA INDONESIA SEBAGAI PENUNJANG PERKULIAHAN FTIK UNISNU JEPARA - Yushinta Eka Farida (Universitas PGRI Semarang, 2017)
Research and Development methods are used in this research. The objective of the research is to develop teaching materials focused on the criteria and quality. This instructional material as a guidebook of the subject course to improve student’s learning in the classroom, so the students got the understanding and improved skills in learning the Indonesian language. This instructional material, as a reference to the Indonesian language for students of PBI UNISNU Jepara is to improve students’ motivation and increase their understanding in self-learning. This textbook development procedure consists of 4 stages: planning, organizing, implementation, and evaluation. This textbook is created by the lecturer, are given suggestion by expert and peers (in peer review section). This teaching book is then evaluated the quality by the lecturers who are appointed as assessors and students as a filling instrument practicality of the textbook. Quality data obtained from the descriptive analysis is then changed into the score. This category is then converted into a conversion score in order to know the quality and value of textbooks used in the learning process of teaching Indonesian language courses.